The impact of attitudinal factors on intention to report workplace Internet abuse. Issue 2 (2nd April 2016) - Campbell, Matt; Stylianou, Antonis C.; Shropshire, Jordan
ABSTRACT: Why do employees actually report workplace Internet abuse? The prevailing theory is that employees make deliberate, calculated decisions only after weighing the pros and cons of reporting. This research proposes a behavioral model in which attitudinal factors are largely responsible for shaping employee intentions to report workplace Internet abuse. Theories of idealism, perceived organizational risk, social influence, and managerial position are synthesized to better understand workers' motivations. A survey 315 American workers tested the proposed hypotheses and research model using structural equation modeling. Results confirm the validity of the proposed model. Each of the attitudinal factors had a significant impact on employee willingness to report Internet violations. This study underscores the importance of attitudinal factors in a space that primarily portrays employees as rational, unemotional actors.